2017
DOI: 10.1007/978-3-319-70022-9_8
|View full text |Cite
|
Sign up to set email alerts
|

Shape It – The Influence of Robot Body Shape on Gender Perception in Robots

Abstract: Abstract. Previous research has shown that gender-related stereotypes are even applied to robots. In HRI, a robot's appearance, for instance, visual facial gender cues such as hairstyle of a robot have successfully been used to elicit gender-stereotypical judgments about male and female prototypes, respectively. To complement the set of features to visually indicate a robot's gender, we explored the impact of waist-to-hip ratio (WHR) and shoulder width (SW) in robot prototypes. Specifically, we investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 14 publications
2
34
0
1
Order By: Relevance
“…These findings are consistent with prior research indicating the automaticity at which social biases extend to and affect behavior in HRI (e.g., [17], [21], [22], [46], [30]). Moreover, the findings support indications by a growing body of literature (containing instances of unprovoked abuse towards robots -e.g., [47], [48]; as well as less empathy for robots relative to that for people when witnessing or participating in their abuse -e.g., [49], [50]) that people more readily engage in the dehumanization of robots.…”
Section: B Links To Existing Literature and Broader Implicationssupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with prior research indicating the automaticity at which social biases extend to and affect behavior in HRI (e.g., [17], [21], [22], [46], [30]). Moreover, the findings support indications by a growing body of literature (containing instances of unprovoked abuse towards robots -e.g., [47], [48]; as well as less empathy for robots relative to that for people when witnessing or participating in their abuse -e.g., [49], [50]) that people more readily engage in the dehumanization of robots.…”
Section: B Links To Existing Literature and Broader Implicationssupporting
confidence: 92%
“…Even when robots lack explicit gendering, the automaticity at which people categorize and make inferences on the basis of gender nevertheless influences the human-robot interaction dynamics. For example: genderstereotypic cues in a robot's morphology and head-style are enough to prompt the attribution of gender to an otherwise agendered robot [21], [22]; the perception of a robot as gendered prompts different evaluations of its likability [23]; and nonconformity of a robot's behavior relative to extant stereotypes associated with its gendering reduces user acceptance [24]. Thus, it is not surprising that antisocial behavior in the form of gender-based stereotyping, bias, and aggression extends to human-like interactions with gynoids.…”
Section: A Associations Between Gendering and Dehumanizationmentioning
confidence: 99%
“…Previous research has shown that people use these social categories even in impression formation about nonhuman entities [11,13]. For instance, manipulation of a robot's body shape [1] or hairstyle in a gender stereotypical fashion elicits the perception of gender in robots [11,23,33].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for instance, people have different expectations of humanoid robots than they do of robots shaped like machines (Hegel et al 2008; Kwak 2014) or animals (Lee, Lau, and Hong 2011) and can quickly identify a robot as being a robot dog or a robot cat or an android. 4 Similarly, people are remarkably quick to attribute gender to robots, and their relationships with robots are shaped by whether they are interacting with a “male” or “female” robot (Bernotat, Eyssel, and Sachse 2017; Eyssel and Hegel 2012; Otterbacher and Talias 2017; Robertson 2018; Siegel, Breazeal, and Norton 2009).…”
Section: How Robots Have Racementioning
confidence: 99%